A single amino acid substitution in the VP2 protein of Indian foot‐and‐mouth disease virus serotype O vaccine strain confers thermostability and protective immunity in cattle. Issue 6 (23rd October 2022) - Biswal, Jitendra K.; Sreenivasa, Beeragere Parameshwaraiah; Mohapatra, Jajati K.; Subramaniam, Saravanan; Jumanal, Veena; Basagoudanavar, Suresh H.; Dhanesh, Valia Valappil; Hosamani, Madhusudan; Tamil Selvan, Ramasamy Periyasamy; Krishnaswamy, Narayanan; Ranjan, Rajeev; Pattnaik, Bramhadev; et al.
Abstract: Foot‐and‐mouth disease (FMD) is a significant threat to animal health globally. Prophylactic vaccination using inactivated FMD virus (FMDV) antigen is being practised for the control in endemic countries. A major limitation of the current vaccine is its susceptibility to high environmental temperature causing loss of immunogenicity, thus necessitating the cold chain for maintenance of its efficacy. Hence, the FMD vaccine with thermostable virus particles will be highly useful in sustaining the integrity of whole virus particle (146S) during storage at 4°C. In this study, 12 recombinant mutants of Indian vaccine strain of FMDV serotype O (O/IND/R2/1975) were generated through reverse genetics approach and evaluated for thermostability. One of the mutant viruses, VP2_Y98F was more thermostable than other mutants and the parent FMDV. The oil‐adjuvanted vaccine formulated with the inactivated VP2_Y98F mutant FMDV was stable up to 8 months when stored at 4°C and induced protective antibody response till dpv 180 after primary vaccination. It is concluded that the VP2_Y98F mutant FMDV was thermostable and has the potential to replace the parent vaccine strain.